2015
DOI: 10.1159/000438460
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate Variability Independently Predicts Renal Prognosis in Advanced Chronic Kidney Disease Patients

Abstract: Background: We often experience visit-to-visit estimated glomerular filtration rate (eGFR) variability among patients with advanced chronic kidney disease (CKD). However, the impact of eGFR variability on renal prognosis is not well understood. Methods: The Kanagawa Valsartan Trial was a multicenter, randomized, open-label trial that compared the effect of add-on treatment with angiotensin II receptor blocker, valsartan, with that of conventional treatment on the rate of CKD progression in 293 advanced CKD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…DOI: 10.1159/000487714 ity tended to be older (median 68 years vs. 62.5 years in low eGFR variability group, p < 0.001) and male (94 vs. 76% in low eGFR variability group). However, similar to our findings, patients with high eGFR variability were 2.1 times more likely to experience progression to ESRD, requiring transplant or dialysis [19]. Authors indicate that visit-to-visit variability in eGFR should be evaluated on a larger scale and that eGFR slope and eGFR variability may be useful in predicting outcomes [19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…DOI: 10.1159/000487714 ity tended to be older (median 68 years vs. 62.5 years in low eGFR variability group, p < 0.001) and male (94 vs. 76% in low eGFR variability group). However, similar to our findings, patients with high eGFR variability were 2.1 times more likely to experience progression to ESRD, requiring transplant or dialysis [19]. Authors indicate that visit-to-visit variability in eGFR should be evaluated on a larger scale and that eGFR slope and eGFR variability may be useful in predicting outcomes [19].…”
Section: Discussionsupporting
confidence: 86%
“…Uehara et al [19] also performed a post hoc analysis of a pharmacologic intervention trial to determine if patients with advanced kidney disease who had higher eGFR variability would hasten their progression to ESRD requiring transplant or dialysis. A total of 237 patients were included in their final analysis and contrary to our findings, patients with high eGFR variabil- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that renal function has little influence on the urine PCR 19 . Moreover, proteinuria declines with glomerulosclerosis and advanced stages of CKD exhibit disturbed circadian blood pressure rhythms 20 , structurally deficient arterioles 21 and eGFR variability 22 . Whether the exception described above is due to the reasons discussed here remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CRIC participants initiating hemodialysis with an antecedent abrupt decline in kidney function (8.5%) experienced, on average, a 3-fold higher risk for death within the first year of dialysis [23]. There is emerging literature suggesting that, independent of long-term GFR trajectory over time, short-term variations in eGFR are predictive of kidney disease outcomes [24][25][26].…”
Section: Discussionmentioning
confidence: 99%